Management of recurrent bleeding from facial arteriovenous malformations in end-stage liver disease - Hussain, Syed Sufyan; Cheent, Kuldeep S; Khan, Shahid A; Jackson, James E; Crossey, Mary ME; Thomas, Howard C; Robinson, Simon D Taylor (International Journal of Hepatology, 2010)
We report the management by arterial embolisation of recurrent significant bleeding from a facial arteriovenous malformation (AVM) in a patient with end-stage liver disease. Given their propensity to re-bleed, AVMs are often refractory to other forms of treatment, including surgery. Evidence from the management of facial AVMs and our case suggests that embolisation may offer a better initial management strategy in patients with end-stage liver disease related facial AVMs. International Journal of Hepatology Vol.1(4) 2010 pp.53-54